Cell-fate transition and determination analysis of mouse male germ cells throughout development - Jiexiang Zhao (Nature Portfolio, 2021)
The full-term developmental profile of male germ cells remains undefined. Here, the authors use single-cell sequencing to investigate the transcriptome landscapes of mouse male germ cells throughout development and find several critical regulators for prenatal cell-fate determination.